Our kind of game : a novel - Copeland, Johanna (Harper, an imprint of HarperCollinsPublishers, 2024)
"2019. Stella Parker has the life she's always wanted: a loving husband, two happy children that she gave up her thriving law career to raise, and a beautiful house in the tony suburbs of Washington, DC. But when her neighbor Gwen shows up at her door, claiming to know things about her, Stella's life is thrown into turmoil and she's forced to reckon with the dark secret upon which she's built her life. 1987. Julie Waits yearns to be a cheerleader--a gateway to a world of normalcy with best friends and sleepovers, and an escape hatch from life with her widowed mother, the terrible men she attracts, and the upheaval caused by their abrupt and constant moves. But when her mother decides those relationships are over, the past becomes a forbidden subject that Julie can never revisit. As Stella probes deeper into what brought Gwen to her door, the answer--and who Julie is to her--become increasingly, terrifyingly, clear--